Urban tree cover change, income and crime assessments in Sao Paulo city, Brazil from 2010-2017 - Arantes, Bruna Lara de (2022)
Sao Paulo city is one of five largest cities in the word, the biggest city of Latin America, and continuing to show consistent urban population growth what makes the city become an important object of study. This thesis aims to contribute to filling the knowledge gap in Latin America cities and offering good quality data to support public policies. In this way, we present in chapter one an UTC Change map to identify where urban tree cover increased, decreased, and did not change in Sao Paulo city from 2010-2017 period. Tree cover was derived from two high resolution images: the Aero Photogrammetric Survey image in 2010 (1m2) and a Worldview-2 image from 2017 (70 cm) and were classified through a supervised object-oriented classification with the Random Forest. And the results pointed to XX net change in most urbanized areas of the city and XX net change in the most forest areas of the city, with domain of private land use in the city. In the Chapter two we analyzed the spatial correlation between tree cover and per capita income and the interaction of these variables with other land covers (lawn, buildings and shadows), to 2010 year. The results present that the city of São Paulo has an uneven distribution between tree cover and income, present positive spatial correlation to urbanized areas. In the chapter three we propose test the tree cover and crime spatially dependence, and once this occurs, several spatial models was carried out with potential confounders controlled. Our main results showed that Sao Paulo city tree cover is associated with lower total, property and person crime rates, even when different areas of the city, scales of study, and denominator of crime are tested. The results follow the literature that have observed tree cover associated with lower crime rates, for different types of crime.